DAYA DUKUNG PERATURAN DAERAH KOTA BANDUNG UNTUK PENERTIBAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA - Sudaryat - (Jurnal Hukum dan Bisnis (Selisik), 2021)
Bandung city is a shopping tourism city. As a tourist destination, this city cannot be separated from the existence of street vendors who on the one hand cause urban irregularities but on the other hand have absorbed labor and increased local revenue. The purpose of this study was to obtain a juridical study of the carrying capacity of the Bandung City regional regulations in empowering and controlling street vendors. The results of the study show that the current Bandung City Regulations related to street vendors have not fully supported the empowerment of street vendors and have only touched on the controlling aspect and even then it is still not optimal. In addition, the Bandung City Regional Regulation related to street vendors must support the mission of the city of Bandung as a shopping tourism city not only from the side of control but also from the empowerment side only to make the city of Bandung clean and orderly but create a safe business environment, create jobs and increase local revenue for the city of Bandung